Status of Members in Unions during Appeal from a Penalty Imposed by the Local Union - Taft, Philip (Quarterly Journal of Economics, 1948)
Journal Article Status of Members in Unions during Appeal from a Penalty Imposed by the Local Union Get access Philip Taft Philip Taft Brown University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 4, August 1948, Pages 610–616, https://doi.org/10.2307/1881768 Published: 01 August 1948